A Comparative Study Of Cryptocurrency Ability As Hedge And Safe Haven During The Covid-19 Pandemic - Didik Gunawan (The Indonesia Capital Market Institute, 2021)
This study tries to prove whether dogecoin can be a hedging tool and or a safe haven like bitcoin and tether. The population of this study is all Bitcoin (BTC), Tether (USDT), Dogecoin (DOGE) and S&P 500 data with daily time series data. While the data used as a sample in this study will be divided into two parts, daily closing data that follows the opening of trading in S&P 500 stocks before the WHO announcement about the global pandemic (12 March 2020) and during the pandemic. The results show that Bitcoin and Dogecoin can act both as hedging tools and as safe havens, while Tether can only be a hedging tool but cannot be a safe haven. These results prove that even though stablecoins are guaranteed by fiat money, they have not become investors' choice as a safe haven, fears of hacking and moral hazard are allegedly the main reasons